Desempenho do capim-açú e do capim-canarana em função da adubação com nitrogênio e potássio - Araujo, Ivo Guilherme Ribeiro de [UNESP] (2015)
The Maranhão downloaded is an important ecosystem of the Brazilian Amazon, and represents a significant agricultural frontier, with production typically the pasture, is characterized by high richness of species with forage potential, especially the grass açu (Paspalum plicatulum Mich). However, due to lack of information for proper nutritional management of açú grass and its morphogenesis it has been replaced by pastures of exotic species, such as the grass canarana (Echinochloa pyramidalis). This study aimed to evaluate the performance of grass açu and canarana grass through their agronomic characteristics and morphogenetic subjected to nitrogen (N) and potassium (K) fertilization. The agronomic characteristics (leaf area, dead material, live tillers, dead tillers, thatched production, leaf production, fodder production) and morphogenetic and structural leaf appearance rate (LAR), thatched stretching rate (TALC) rate sheet stretching (TALF), phyllochron (FILO), leaf senescence time (TSF), final leaf length (LOA). The experiment was conducted in a greenhouse, with soil and seedlings were collected in the region of Maranhão Lowlands, and the soil characterized as Plinthosol Argilúvico. The experimental design was completely randomized with factorial arrangement 2 x 5 x 2 (2 species, five doses of N and K two doses) totaling 20 treatments and four repetitions, totaling 80 experimental units. The treatments were the nitrogen rates: 0, 50, 100, 150 and 200 mg/dm3 and two levels of potassium fertilization: 10 and 30 mg/dm3. The dry matter production of grass Sugar has a lower response to nitrogen fertilization that the grass canarana. The grass açú is more production leaves the grass canarana, in smaller doses of N. The tillering responded positively to treatment with nitrogen, and the grass caiman species with higher production of tillers. The morphogenesis TApF, TALC are not influenced by N rates or by combinations of doses ...